Optimal income taxation, public goods provision and robust mechanism design - Felix Bierbrauer (Max Planck Institute for Research on Collective Goods, 2008)
This paper extends the model of optimal income taxation due to Mirrlees (1971) and includes private information on public goods preferences. A mechanism design approach is used to establish the following result: If policies are required to be robustly implementable in the sense of Bergemann and Morris (2005), then the optimality conditions in the extended model with uncertainty about tax and expenditure policies, are the same as in the standard model of optimal income taxation. The paper provides a foundation for a widely used assumption in public nance, namely that individuals optimize their behaviour subject to a predetermined and commonly known tax system.
Keywords: D71; D82; H21; H41; 330; Optimal Taxation; public goods provision; Revelation of Preferences; Optimale Besteuerung; Öffentliches Gut; Mechanism; Offenbarte Präferenzen; Theorie